The Effect of Group Counseling with Self-Control Technique to Reduce Online Game Addiction among Students - Alfa Hendarsyah; Christine Masada Hirashita Tobing; Evi Fitriyanti (Asosiasi Asesmen Pendidikan (AAP), 2025)
The phenomenon of online game addiction among students has caused various negative impacts, such as a decline in academic achievement, lack of social interaction, and decreased responsibility in daily life. This condition indicates the need for structured counseling interventions. This study employed a quantitative approach with a quasi-experimental design using a pre-test and post-test control group design. The sampling technique was purposive sampling involving 40 students of SMA Muhammadiyah Cipanas, divided into an experimental group and a control group. The experimental group received three informational services and seven sessions of group counseling using the self-control technique, while the control group only received three informational services. The research instruments included a Likert-scale questionnaire, observation, interview, and documentation. Data were analyzed using an Independent Sample T-Test with the assistance of SPSS. The results showed a significant difference between the experimental and control groups (t = 2.152; p < 0.05), indicating that group counseling with the self-control technique was effective in reducing online game addiction. This finding was supported by observations and interviews, which revealed students’ improved ability to manage gaming time and academic responsibilities. Thus, self-control-based group counseling proved to be relevant and can serve as a practical counseling strategy in schools.